Alternatively-spliced lncRNA-PNUTS promotes HCC cell EMT via regulating ZEB1 expression. Issue 1 (February 2023) - Zhao, Haiyan; Liu, Chang; Zhao, Chongyu; Che, Chi; Liu, Wuguang; Mei, Yan
Background: Long non-coding RNAs have been implicated in various cancers as they regulate critical cellular processes such as proliferation, migration, invasion, and apoptosis in tumorous tissues. lncRNA-PNUTS is newly reported as an alternatively-spliced lncRNA from PNUTS pre-mRNA that promotes oncogenesis in breast cancer. However, whether LncRNA-PNUTS plays a role in other forms of cancers, such as liver cancer, remains unknown. Method: In the current study, we investigated the potential role of lncRNA-PNUTS in hepatocellular carcinoma (HCC). The levels of lncRNA-PNUTS in tumorous tissues obtained from HCC patients were measured. The potential impacts of lncPNUTS on metastasis and invasion were investigated through gain- or loss- of function experiments in cell models of liver cancers, as well as other cellular assays such as trans-well assays and wound-healing assays. Results: Here, we report that lncPNUTS was upregulated in human HCC tissues. Loss- and gain-of-function experiments indicated lncPNUTS promoted metastasis and invasion. In addition, ZEB1, which is involved in the activation of epithelial-mesenchymal-transition (EMT), was identified as a downstream target of lncPNUTS. Conclusion: Our findings indicated lncPNUTS promotes HCC cancer cell metastasis and invasion via targeting ZEB1 to activate the EMT pathway, suggesting that lncPNUTS is a potential prognostic marker and therapeutic target for HCC patients.